2007
DOI: 10.1063/1.2472281
|View full text |Cite
|
Sign up to set email alerts
|

Probing of a surface plasma wave by an obliquely incident laser on the metal surface

Abstract: A surface plasma wave ͑SPW͒ of frequency 1 and wave number k 1 propagating along a metal-free space boundary exerts a ponderomotive force on the free electrons, creating an electron density perturbation at frequency 2 1. When a laser of frequency 2 and wave number k 2 is incident at a suitable angle on the metal surface, it gives rise to the oscillatory velocity of electrons at frequency 2. This oscillatory velocity couples with the density perturbation to generate a nonlinear current at frequency 2 1 + 2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…At lower values of frequency, the effect of the pump amplitude is not noticeable, but as the frequency increases, the power increases with the increase in the amplitude of the pump field. This result is in line with the theoretical investigation of Singh et al Figure shows that the frequency of the emitted THz radiation increases with the wiggler wave vector, and from the relations k0=2πλ0 and λ1=λ02γ02 (where λ 0 is the wiggler period and λ 1 is the emitted radiation wavelength), the wiggler period decreases with the increase in wiggler wave vector, and consequently the frequency of the output radiation can be increased by reducing the wiggler period.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…At lower values of frequency, the effect of the pump amplitude is not noticeable, but as the frequency increases, the power increases with the increase in the amplitude of the pump field. This result is in line with the theoretical investigation of Singh et al Figure shows that the frequency of the emitted THz radiation increases with the wiggler wave vector, and from the relations k0=2πλ0 and λ1=λ02γ02 (where λ 0 is the wiggler period and λ 1 is the emitted radiation wavelength), the wiggler period decreases with the increase in wiggler wave vector, and consequently the frequency of the output radiation can be increased by reducing the wiggler period.…”
Section: Resultssupporting
confidence: 91%
“…Singh et al studied the excitation of SPW by using a laser incident obliquely on the free space interface and observed that the power of the output radiation can be increased monotonically by increasing the frequencies of the laser and the SPW field.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SPW induced harmonic generation and other nonlinear effects from metallic surfaces have attracted significant attention. [21][22][23][24][25][26][27][28][29][30][31] Li et al 32 carried out simulations to investigate plasmon gap modeassisted third-harmonic generation from metal film coupled nanowires. The plasmon gap resonance enhances the third harmonic intensity by four orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%